2016
DOI: 10.3324/haematol.2015.139626
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel stereotypic IGHV4-59/IGHJ5-encoded B-cell receptor subset expressed by various B-cell lymphomas with high affinity rheumatoid factor activity

Abstract: Subsets of mucosa-associated lymphoid tissue (MALT) lymphoma, splenic marginal zone B-cell lymphoma (MZBCL) and chronic lymphocytic leukemia (CLL) have been identified that express near-identical B-cell receptors (BCRs), strongly suggesting selection by restricted antigenic epitopes. We here report a new IGV mutated stereotypic IGHV4-59/IGHJ5-encoded BCR subset expressed in hepatitis C virus (HCV)-related B-cell lymphoma, MALT lymphoma and diffuse large B-cell lymphoma (DLBCL). We demonstrate that these mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 20 publications
5
32
0
Order By: Relevance
“…In vitro binding analysis of the recombinant antibodies from the representative MALT lymphoma associated IGHV1-69 or IGHV3-7 rearrangements confirms their activities to the Fc portion of human IgG [42]. Moreover, strong RF activities are also demonstrated for recombinant antibodies from two MALT lymphomas that harbour classic RF IGHV1-69/IGHJ4 rearrangement, but not yet meet the criteria for a high homology to a RF CDR3 sequence, and additionally from a HCV-associated MALT lymphoma that harbours a novel IGHV4-59/IGHJ5 stereotypic rearrangement [42,63]. These findings indicate that the true frequency of MALT lymphomas that express BCR bearing RF activities is underestimated.…”
Section: Ii) Properties Of Immunoglobulin Expressed By Malt Lymphomasupporting
confidence: 52%
“…In vitro binding analysis of the recombinant antibodies from the representative MALT lymphoma associated IGHV1-69 or IGHV3-7 rearrangements confirms their activities to the Fc portion of human IgG [42]. Moreover, strong RF activities are also demonstrated for recombinant antibodies from two MALT lymphomas that harbour classic RF IGHV1-69/IGHJ4 rearrangement, but not yet meet the criteria for a high homology to a RF CDR3 sequence, and additionally from a HCV-associated MALT lymphoma that harbours a novel IGHV4-59/IGHJ5 stereotypic rearrangement [42,63]. These findings indicate that the true frequency of MALT lymphomas that express BCR bearing RF activities is underestimated.…”
Section: Ii) Properties Of Immunoglobulin Expressed By Malt Lymphomasupporting
confidence: 52%
“…39,40,44,45 IGHV1-69 and IGHV4-59 genes are frequently expressed in HCVrelated B-cell disorders, namely MC B-cell clones producing rheumatoid factors and HCV-associated B-cell NHLs, and in other autoimmune diseases. 18,[20][21][22][23][24]46 Remarkably, these IGHV genes were more frequently used by NCS memory B cells of HCVinfected patients than those of healthy individuals (Figure 4). Thus, even in HCV patients without clinically detectable lymphoproliferation, there is a disease-associated disturbance of the BCR immunoglobulin gene repertoire, most pronounced in NCS memory B cells, with a significantly increased usage of those IGHV genes mainly involved in autoantibodies and pathological clonal B-cell expansions in HCV-infected patients.…”
Section: Discussionmentioning
confidence: 98%
“…Based on these observations, we expect that the antibody from patient SS204, when expressed as IgM, will display in vitro RF activity. We and others have shown on several occasions that these stereotypic V1–69 RFs all exhibit RF activity when expressed as IgM antibodies . Thus, all clonally expanded CD21 −/low B cells from the 3 SS patients exhibit poly‐ and/or autoreactivity.…”
mentioning
confidence: 80%
“…Previously, we identified 4 cases of HCV‐associated lymphomas, which were originally described by Ng et al , that also expressed stereotypic RFs, i.e., V4–59 RFs and V4–59/J H 5 RFs . From these lymphomas Ng and colleagues produced recombinant IgG antibodies, in the same system as that used by Glauzy et al , which were reported to have no in vitro RF activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation